Perspective: Current Scientific Evidence and Research Strategies in the Role of Almonds in Cardiometabolic Health - Paula R Trumbo; Jamy Ard; France Bellisle; Adam Drewnowski; Jack A Gilbert; Ronald Kleinman; Anoop Misra; John Sievenpiper; Maha Tahiri; Karol E Watson; James Hill (Current Developments in Nutrition)
Almonds are consumed by individuals around the world. Because almonds are rich in protein, unsaturated fatty acids, and fiber, a significant amount of research has been conducted on their role in affecting various cardiometabolic endpoints (body weight, blood pressure, blood cholesterol levels, and glycemic response). The most current meta-analyses on almond consumption and various health-related endpoints suggest that almond consumption does not result in weight gain and results in small reductions in LDL cholesterol and diastolic blood pressure, as well as improved glycemic responses in certain populations (i.e. Asian Indians). A number of research gaps on almond consumption and cardiometabolic health were identified that should be addressed to further understand their role in the various cardiometabolic endpoints, including the mechanisms of action interactions with the microbiome with regular consumption and their role as part of a healthy dietary pattern for both individuals and the general population.